2015
DOI: 10.1186/s13620-015-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Prevalence and Seasonality of Fasciola hepatica in Pasture-based Dairy herds in Ireland using a Bulk Tank Milk ELISA

Abstract: BackgroundFasciola hepatica is a helminth parasite of global importance in livestock, with major economic impact. However information on F. hepatica infections in Irish pasture-based dairy herds is limited. Therefore this study was conducted in order to determine the prevalence, seasonality and management factors associated with F. hepatica. A total of 319 Irish dairy herds were selected for this study. Bulk tank milk (BTM) samples were collected from 290 dairy farms on a quarter year basis, while from a furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…This test has very similar performance to other ELISA based tests used to assess fluke prevalence and seasonal variation thereof, allowing for cross‐comparison (e.g. Ildana Biotech Kit, Dublin, Ireland, with a reported SE/SP of 98%; Bloemhoff et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This test has very similar performance to other ELISA based tests used to assess fluke prevalence and seasonal variation thereof, allowing for cross‐comparison (e.g. Ildana Biotech Kit, Dublin, Ireland, with a reported SE/SP of 98%; Bloemhoff et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The disease results in important economic losses to the agricultural community globally, as well as being an highly prevalent food-borne zoonosis, with 180 million of people at risk [1][2][3][4]. F. hepatica infection has a prevalence of 76% in cattle in the Republic of Ireland, and an estimated prevalence of 78% in the UK [5,6]. Due to the increase in anthelmintic resistance in parasite populations, and the inherent difficulties in developing anthelmintics [7][8][9], a vaccine-based approach to aid in the control of fasciolosis is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…A recombinant mutant version of FhCL1 (rmFhCL1), expressed in Saccharomyces cerevisiae or Pichia pastoris [23,27], which does not autocatalytically activate, is useful as a reliable immunodiagnostic tool in Fasciola hepatica infections in cattle [5,28]. rmFhCL1 has also been used as a vaccine antigen that was capable of reducing fluke burdens in cattle by 48.2 % [29]; However, other trials have not shown a similar reduction in fluke burden, although in a study with goats, a significant decrease in liver pathology was found [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These molecules were selected since (i) they are produced by adult flukes and thus continue stimulating the immune system during the chronic phase of the illness, and (ii) Fasciola cathepsins L1, L2, and L5 contain a common epitope recognized by mAb MM3, which is the capture antibody in the MM3-SERO ELISA (Mezo et al 2007). Although rFhpCLs from the L1 clade have already been successfully used to develop a very sensitive and specific lateral flow test for immunodiagnosis of human fascioliasis , as well as to design ELISA tests for human (O'Neill et al 1999;Carnevale et al 2001a, b;Gonzales Santana et al 2013;Gottstein et al 2014) and animal use (Cornelissen et al 2001;Kuerpick et al 2013;Selemetas et al 2014;Bloemhoff et al 2015), the performance of rFhpCLs from L2 and L5 clades as ELISA targets has not previously been investigated. From a functional point of view, a single amino acid substitution may be sufficient to affect substrate specificity in cysteine proteases from F. hepatica (Smooker et al 2000).…”
Section: Discussionmentioning
confidence: 99%